Cobalt Oxide Nanoparticles/Graphene/Ionic Liquid CrystalModified Carbon Paste Electrochemical Sensor for Ultra-sensitiveDetermination of a Narcotic Drug - Nada Farouk Atta; Ahmed Galal; Ekram Hamdy El-Ads; Samar Hamed Hassan (Tabriz University of Medical Sciences, 2019)
Purpose: Drug-abuse, namely morphine (MO) affects the metabolism of neurotransmitterssuch as dopamine (DA). Therefore, it is crucial to devise a sensitive sensing technique tosimultaneously determine both compounds in real samples.Methods: The fabrication of the sensor is based on in situ modification of a carbon paste (CP)electrode with cobalt oxide nanoparticles, graphene, and ionic liquid crystal in presence ofsodium dodecyl sulfate; CoGILCCP-SDS. The modified sensor is characterized using scanningelectron microscopy, electrochemical impedance spectroscopy and voltammetry measurements.Results: Electron transfer kinetics and analytical performance of the proposed sensor wereenhanced due to the synergistic role of all the modifiers. The simultaneous determination of MOand DA achieved low detection limits of 0.54 nmol L−1 and 0.25 nmol L−1, respectively. Besides,a carbon-based electrochemical sensor is fabricated for the nano-molar determination of MOin real samples and formulations. The sensor showed fouling resistance and anti-interferenceability in presence of other species in human fluids. The real sample analysis of MO wassuccessfully achieved with good recovery results in urine samples and pharmaceutical tablets.Linear dynamic range, sensitivity, detection limit and quantification limit of MO in urine were5 nmol L−1 to 0.6 μmol L−1, 6.19 μA/μmol L-1, 0.484 nmol L−1 and 1.61 nmol L−1, respectively.Conclusion: This sensor has great ability to be extended for electrochemical applications inassaying of many drugs.